2000
DOI: 10.1007/bf02976571
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative phenolic compounds from the roots ofRhodiola sachalinensis A. Bor

Abstract: The acetone extract of the roots of Rhodiola sachalinensis has furnished six phenolic compounds which exhibited significant scavenging effects against DPPH free radical. The structures of these compounds were identified and determined as gallic acid (1), (-)-epigallocatechin 3-O-gallate (2), kaempferol (3), kaempferol 7-O-alpha-L-rhamnopyranoside (4), herbacetin 7-O-alpha-L-rhamnopyranoside, (5) and rhodiolinin (6) by physico-chemical and spectral evidences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 4 publications
0
49
0
1
Order By: Relevance
“…Rhodiola rosea L. (Crassulaceae), an herbaceous plant, is used in Asian and Eastern European traditional medicines for its pressure-reducing [4], neurosystem-stimulating [5], fatigue-removing [6], hypobaropathy-preventing [7], antidepressive [7], anticancer [8], antiaging [9], cardiovascular-protective [10], and hepatoprotective effects [11]. Chemical investigations on this plant have revealed many chemical entities, including phenolic acids [12], phenolethanoids [13], phenylpropenoids [14], flavonoids [15], monoterpenes [4], and glycosides [16]. In a preliminary biological evaluation, crude extracts of R. rosea roots exhibited inhibitory activities toward MMP-2 and collagenase at a concentration of 100 µg/mL [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodiola rosea L. (Crassulaceae), an herbaceous plant, is used in Asian and Eastern European traditional medicines for its pressure-reducing [4], neurosystem-stimulating [5], fatigue-removing [6], hypobaropathy-preventing [7], antidepressive [7], anticancer [8], antiaging [9], cardiovascular-protective [10], and hepatoprotective effects [11]. Chemical investigations on this plant have revealed many chemical entities, including phenolic acids [12], phenolethanoids [13], phenylpropenoids [14], flavonoids [15], monoterpenes [4], and glycosides [16]. In a preliminary biological evaluation, crude extracts of R. rosea roots exhibited inhibitory activities toward MMP-2 and collagenase at a concentration of 100 µg/mL [17].…”
mentioning
confidence: 99%
“…Flash column separation of this layer over silica gel afforded three previously unreported chemical entities (1-3) along with twentyfour known compounds. The known compounds were identified to be methyl 4-hydroxybenzoate (4) [18], β-sitosterol (5) [19], (Z)-2-methyl-6-oxo-2-hepten-1-ol (6) [20], gallic acid (7) [21], 4-hydroxyphenyl-2-ethyl β-D-glucopyranoside (8) [22], tyrosol (9) [23], methyl gallate (10) [24], p-coumaric acid (11) [25], caffeic acid (12) [25], aspergillol B (13) [26], 2R,3R-dihydrokaempferol (14) [27], (E)-2-methyl-6-oxo-2-hepten-1-ol (15) [33], creoside III (25) [33], salidroside (26) [34], and icariside D2 (27) [35] based on spectroscopic data analysis and comparison to the literature. Compound 1, obtained as amorphous white powder, had a formula of C 41 H 32 O 24 , as determined using 13 (C-5), δ H 2.12 (H 3 -7)/δ C 211.4 (C-6) and 43.7 (C-5) and δ H 4.22 (H-1′)/δ C 75.6 (C-1) indicated that the aglycone of 2 was connected with the C-1′ of β-D-glucopyranoside via an ether linkage to form creoside I.…”
mentioning
confidence: 99%
“…The therapeutic compounds isolated from this plant have anti-diabetic (Cheng et al, 1993), sedative, hypnotic, anti inflammatory, anti-oxidant potential (Choe et al, 2012;Lee et al, 2000) and hepatoprotective effects (Nan et al, 2003b). The root extract has protective effect in the liver injury of rat model induced by continuous administration of CCl4.…”
Section: Rhodiola Sachalinensismentioning
confidence: 99%
“…19 Moreover, Rhodiola extract contains other antioxidant compounds such as p-tyrosol, organic acids (gallic and caffeic acids), and flavonoids (catechins and proanthocyanidins). 16,37,38 Indeed, there is experimental evidence that treatment of spontaneously hypertensive rats (SHR) with Rhodiola increased the superoxide dismutase activity. 39 Clearly, the anti-inflammatory and antioxidant attributes of Rhodiola can be expected to yield therapeutic benefits in PH.…”
Section: Rhodiola In Ph: Illusionary or Promising?mentioning
confidence: 99%